2010
DOI: 10.1111/j.1365-2834.2010.01166.x
|View full text |Cite
|
Sign up to set email alerts
|

Going blank: factors contributing to interruptions to nurses’ work and related outcomes

Abstract: Nurse leaders should examine ways in which nurses' work can benefit from system improvements to reduce interruptions that lead to patient safety issues such as treatment delays and loss of concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 26 publications
(32 reference statements)
2
62
0
9
Order By: Relevance
“…Variations in the nurse's work environment shaped both the origin of and response to the error and impacted the ability of the nurse to provide high quality care (Steege, Drake, Olivas & Mazza, 2015). The contributions of complex environmental factors that characterize nursing work and lead to failures in delivery of care are well documented in the literature (Sitterding, Ebright, Broome & Patterson, 2014;Foroungi, Weber et al 2013;Hopkinson & Jennings, 2013;Ebright, 2010;Hall et al, 2010;). That nurses participating in this study were able to recall details surrounding an error supports the notion that retrieving details of an event from those involved in the situation is a productive method for learning why things happened the way they did.…”
mentioning
confidence: 99%
“…Variations in the nurse's work environment shaped both the origin of and response to the error and impacted the ability of the nurse to provide high quality care (Steege, Drake, Olivas & Mazza, 2015). The contributions of complex environmental factors that characterize nursing work and lead to failures in delivery of care are well documented in the literature (Sitterding, Ebright, Broome & Patterson, 2014;Foroungi, Weber et al 2013;Hopkinson & Jennings, 2013;Ebright, 2010;Hall et al, 2010;). That nurses participating in this study were able to recall details surrounding an error supports the notion that retrieving details of an event from those involved in the situation is a productive method for learning why things happened the way they did.…”
mentioning
confidence: 99%
“…[6][7][8]11,12 In addition, results of the pilot practice change support earlier reports that the majority of interruptions during medication administration are avoidable and may lead to adverse consequences for patients. 16,31 The greatest impact of implementing the NUPASS guidelines was the significant decrease in avoidable interruptions, particularly those related to phone calls. Successfully decreasing interruptions related to phone calls was highly dependent on teamwork and highlights the important role of support staff in prioritizing and managing phone calls during peak scheduled medication administration times.…”
Section: Discussionmentioning
confidence: 99%
“…McGillis Hall et al (2010) found that nurses identified noise as a frequent distraction during their working day; the critical care unit has a high use of alarms that are vital in alerting staff in changes in patient condition but can also be viewed as a distraction. Health care provided within critical care units commonly involves multiple teams.…”
Section: Is Intensive/critical Care Different?mentioning
confidence: 99%
“…Communication and collaboration is vital for patient safety, however, team members must be aware of the impact of interruptions during medication administration. McGillis et al, (2010) found that the main source of interruptions was attributed to health care providers within the unit.…”
Section: Is Intensive/critical Care Different?mentioning
confidence: 99%